RANCANG BANGUN SISTEM PAKAR MENDIAGNOSA PENYAKIT OBSESSIVE COMPULSIVE DISORDER DENGAN METODE DEMPSTER SHAFER - Nidia Enjelita; Adawiyah, Robiatul (Universitas Methodist Indonesia, 2019)
Anxiety is a normal reaction to stress and can be beneficial in some situations. It can alert us to dangers and help us prepare and pay attention. Anxiety disorders differ from normal feelings of nervousness or anxiousness and involve excessive fear or anxiety. Anxiety disorders can cause people to try to avoid situations that trigger or worsen their symptoms. There are several types of anxiety disorders, including Obsessive-Compulsive Disorder. Obsessive-Compulsive Disorder (OCD) is a disorder in which people have recurring, unwanted thoughts, ideas, or sensations (obsessions) that make them feel driven to do something repetitively (compulsions). Repetitive behaviors, such as hand washing, checking on things, or cleaning, can significantly interfere with a person’s daily activities and social interactions. This Expert system which implements Dempster Shafer Method can help anyone to make sure that they have OCD and need psychologist help to prevent this distress from becoming worst.